2016
DOI: 10.1038/bcj.2016.78
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenases inhibition eradicates leukemia stem cells while sparing normal progenitors

Abstract: The vast majority of patients with acute myeloid leukemia (AML) achieve complete remission (CR) after standard induction chemotherapy. However, the majority subsequently relapse and die of the disease. A leukemia stem cell (LSC) paradigm has been invoked to explain this failure of CR to reliably translate into cure. Indeed, LSCs are highly enriched in CD34+CD38− leukemic cells that exhibit positive aldehyde dehydrogenase activity (ALDH+) on flow cytometry, these LSCs are resistant to currently existing treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…DSF has anti-cancer activity in vitro and in vivo (Irving and Daniel, 1987;Kast and Belda-Iniesta, 2009;Lin et al, 2011;Morrison et al, 2010;Rezk et al, 2015;Yip et al, 2011). Dimethyl ampal thiolester (DIMATE), an ALDH1 and ALDH3 inhibitor, depletes leukemia stem cells but, importantly, does not affect hematopoietic stem cells (Venton et al, 2016). More recently a potent ALDH1A1 selective inhibitor and a pan-ALDH1A inhibitor were found to synergize with chemotherapy (Huddle et al, 2018;Yang et al, 2018), whereas an ALDH-targeted pro-drug effectively eliminated ALDH bright melanoma cells (Sarvi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…DSF has anti-cancer activity in vitro and in vivo (Irving and Daniel, 1987;Kast and Belda-Iniesta, 2009;Lin et al, 2011;Morrison et al, 2010;Rezk et al, 2015;Yip et al, 2011). Dimethyl ampal thiolester (DIMATE), an ALDH1 and ALDH3 inhibitor, depletes leukemia stem cells but, importantly, does not affect hematopoietic stem cells (Venton et al, 2016). More recently a potent ALDH1A1 selective inhibitor and a pan-ALDH1A inhibitor were found to synergize with chemotherapy (Huddle et al, 2018;Yang et al, 2018), whereas an ALDH-targeted pro-drug effectively eliminated ALDH bright melanoma cells (Sarvi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…DIMATE is cytotoxic for leukemic stem cells, but not for healthy hematopoietic stem cells. Administration of DIMATE in mice decreases leukemia cells which are derived from acute myeloid leukemia patients and intravenously transplanted [ 122 ]. DIMATE also promotes cell death of melanoma cells and inhibits tumor growth in immunocompetent, immunosuppressed and patient-derived xenograft mouse models [ 123 ].…”
Section: Targeting Lipid Metabolism and Therapy Options For Cancermentioning
confidence: 99%
“…In conclusion, ALDH activity can be used as a functional stem cell marker, identifying HSC population and LSC population in AML. Validity to therapeutically target ALDH in AML treatment is controversial; a recent paper showed that in vitro and in vivo inhibition of ALDH selectively eradicates CD34+/CD38−ALDH+ cells [31]. In this study, the authors used the CD34+/CD38−/ALDH+ phenotype to describe LSC, which is distinct from most other studies that define CD34+/CD38−/ALDH+ to reflect HSC.…”
Section: Identification Of Leukemic Stem Cellsmentioning
confidence: 99%